Valor Histórico de las Haciendas Malqui-Machay y su Contribución al Fortalecimiento de la Identidad Cultural. - Llore Chicaiza, Wendy Sabrina (2020)
The present research project is focused on the recovery of cultural identity giving historical value to the Malqui-Machay estates located in the province of Cotopaxi in La Maná, this site is also known as the last abode of Atahualpa by the relevant historical events for Ecuadorian history since it would have been the refuge of the last Incas Quiteños. However, it presents certain weaknesses regarding the conservation of the cultural identity of the inhabitants in the sector, this is due to the devaluation of archaeological sites that have historical landmarks that are an important source to recover the customs and traditions that develop around the history. With this precedent, the present research has as its purpose the detection of the historical value of the Malqui-Machay estates and their contribution to the strengthening of cultural identity. This study was based on descriptive research in which the criteria of professionals, owners and residents of the Guasaganda village were taken, whose information was collected through 5 interviews and 64 surveys with structured questions, which were analyzed and interpreted with the purpose of knowing the criteria about the Malqui-Machay estates. According to the main results obtained, it can be detailed that the estates contribute to the rescue of cultural identity through the historical events that have occurred in these places. That is why the history of the estates, the most outstanding legends of the sector and the strategies for the conservation of cultural identity were reflected in an informative guide of cultural heritage. With this project a positive impact was obtained since, when recovering part of the cultural identity through the story of the historical events of the estates, a close relationship with tourism will be opened and with it the economic revitalization of the Guasaganda village – La Maná city.